Penyuluhan Protokol Kesehatan Untuk Mencegah Tertularnya Virus Covid-19 Kepada Pedagang Di Pasar Pelas - Naelul Laelatul Rizki; M. Faiz Amiruddin (LP3M IAIFA Kediri, 2021)
In this community service activity, researchers conducted counseling about the importance of maintaining health by implementing health protocols. Seeing the current situation which is very tense regarding the corona-19 virus which is getting worse and spreading everywhere and the number of people who have died affected by the corona virus-19. The health side pays very serious attention to this problem, so this problem is a very important problem to be solved. This work of dedication aims to 1). Reminding the public, traders and also buyers who are in the Pelas market to apply the health protocols that have been set by the government, 2). Provide counseling regarding the application of health protocols in accordance with those set by the government. while the benefits that will be generated in this counseling are 1). Reducing the number of people who do not comply with health protocols, 2). Reducing the number of deaths caused by the Covid-19 virus. The results of this dedication work are that the traders in the Pelas market are wearing masks correctly, the traders in the Pelas market use Handsanitizer to clean their hands, the traders want to keep their distance between traders and their buyers, the traders want to stay away from useless crowds, Traders stay away from mobility and besides that, traders also skyrocket (pray) to Allah SWT.